Feminist epistemology: “Daughters of Quine” - Mijić Jelena (Filozofija i Društvo, 2013)
Feminist epistemology implies an approach to the theory of knowledge, which in its centre sets up feminist issues. The paper analyzes a recent course in the area dealing with feminist epistemology, namely feminist empiricism. Unlike other feminists engaged in epistemology, their goal is to keep the basic concepts of the analytic tradition, but considered in the light of feminist interests. Starting from Quine’s naturalized epistemology, feminist empiricists are introducing different concepts of knowledge and the nature of the knowers, creating a new perspective on the relationship of sociopolitical values and scientific research. The feminist empiricist’s advantage over feminist epistemology approaches outside the analytical framework is precisely in accepting the naturalistic and empiricist approach to gender biases. The aim is to evaluate how successful they are in achieving their ideas, and whether such an approach is acceptable.